2016
DOI: 10.1152/ajpcell.00091.2015
|View full text |Cite
|
Sign up to set email alerts
|

PICK1/calcineurin suppress ASIC1-mediated Ca2+ entry in rat pulmonary arterial smooth muscle cells

Abstract: Herbert LM, Nitta CH, Yellowhair TR, Browning C, Gonzalez Bosc LV, Resta TC, Jernigan NL. PICK1/calcineurin suppress ASIC1-mediated Ca 2ϩ entry in rat pulmonary arterial smooth muscle cells. Am J Physiol Cell Physiol 310: C390 -C400, 2016. First published December 23, 2015; doi:10.1152/ajpcell.00091.2015.-Acidsensing ion channel 1 (ASIC1) contributes to Ca 2ϩ influx and contraction in pulmonary arterial smooth muscle cells (PASMC). ASIC1 binds the PDZ (PSD-95/Dlg/ZO-1) domain of the protein interacting with C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 54 publications
4
20
0
Order By: Relevance
“…Indeed, similar to basal [Ca 2ϩ ] i levels, we also found that SOCE was largely augmented in PASMC from ASIC2 Ϫ/Ϫ mice. Consistent with our previous studies (22,23,25,27,28), this enhanced SOCE response is mediated largely by ASIC1. In addition, pretreatment with PcTX1 abolished the elevation in basal [Ca 2ϩ ] i levels in PASMC from ASIC2 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, similar to basal [Ca 2ϩ ] i levels, we also found that SOCE was largely augmented in PASMC from ASIC2 Ϫ/Ϫ mice. Consistent with our previous studies (22,23,25,27,28), this enhanced SOCE response is mediated largely by ASIC1. In addition, pretreatment with PcTX1 abolished the elevation in basal [Ca 2ϩ ] i levels in PASMC from ASIC2 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 92%
“…The direct interaction between Eag1 and MKRN1 long isoform, but not the short isoform, in HEK293T cells was further validated by the in situ proximity ligation assay (PLA) ( Fig. 1 C ), which detects immunofluorescence signals generated from a pair of oligonucleotide-linked antibodies recognizing two proteins that are in close proximity (<40 nm) ( 25 , 26 , 27 ). Together these observations indicate that Eag1 interacts primarily with the C-terminal region of the long isoform of MKRN1.…”
Section: Resultsmentioning
confidence: 95%
“…increased intracellular Ca 2+ ([Ca 2+ ]i) level can increase calpain activity [14]. Calcineurin is a protein phosphatase known as serine/threonine phosphatase and can be activated physiologically by Ca 2+ /calmodulin during the differentiation of skeletal muscles and the development of osteoclasts in bone [15]. Our present study showed that extracellu-…”
Section: Discussionmentioning
confidence: 53%